Где зимует кузькина мать, или Как достать халявный миллион решений? - Норбеков Мирзакарим Санакулович (АСТ, 2003)
Экземпляры: (20220505) / Инвентарный номер: 36793 / Цена: / Авт.знак: Н 82 / ББК: 88.37